Improved salt tolerance of transgenic tobacco expressing apoplastic yeas-derived invertase - Sonnewald, Uwe; et al. (Plant and Cell Physiology, 2001)
We investigated the salt tolerance of transgenic tobacco, in which yeast invertase is expressed in the apoplastic (Apo-Inv) spaces. Whereas photosynthetic activities in wild-type tobacco in light were inhibited under salt stress, transgenic Apo-Inv tobacco maintained constant photosynthetic activities. The physical appearance of plants under salt stress also indicates that yeast invertase expression in the apoplastic space is beneficial for inducing salt tolerance. Apo-Inv tobacco had a much higher osmotic pressure increase in the cell sap than did wild-type tobacco under this type of stress. The physiological importance of sucrose metabolism under salt stress is discussed.
Keywords: invertase; Nicotiana tabacum; photosynthesis; salt stress; sucrose